2014
DOI: 10.1124/dmd.114.057836
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Arachidonic Acid Metabolism by Rat Cytochrome P450 Enzymes: The Involvement of CYP1As

Abstract: Cytochrome P450 (P450) enzymes mediate arachidonic acid (AA) oxidation to several biologically active metabolites. Our aims in this study were to characterize AA metabolism by different recombinant rat P450 enzymes and to identify new targets for modulating P450-AA metabolism in vivo. A liquid chromatography-mass spectrometry method was developed and validated for the simultaneous measurements of AA and 15 of its P450 metabolites. CYP1A1, CYP1A2, CYP2B1, CYP2C6, and CYP2C11 were found to metabolize AA with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…Compared to the PEG400 vehicle control, OME significantly increased (p < 0.05) levels of 14, 15-EET and 12,13-EpOME in plasma. It has been reported that P450 1A and 2B generate more hydroxy metabolites than epoxy metabolites in vitro (El-Sherbeni and El-Kadi, 2014). Similarly, TPPU alone resulted in a significant increase (p < 0.05) in the level of 12,13-EpOME, a linoleic acid epoxy metabolite (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to the PEG400 vehicle control, OME significantly increased (p < 0.05) levels of 14, 15-EET and 12,13-EpOME in plasma. It has been reported that P450 1A and 2B generate more hydroxy metabolites than epoxy metabolites in vitro (El-Sherbeni and El-Kadi, 2014). Similarly, TPPU alone resulted in a significant increase (p < 0.05) in the level of 12,13-EpOME, a linoleic acid epoxy metabolite (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…EROD, MROD, PROD and BFCOD activities, consistent with P450 1A1, P450 1A2, P450 2B1 and P450 3A1 + P450 1A2 (Yang et al, 2003; Masubuchi et al, 1997; Petrulis et al, 2001; Baer-Dubowska et al, 1998; Donato et al, 2004) were induced with OME; however, this induction was short lived (2 days). These isoforms of P450s also generate EETs (Diani-Moore et al, 2006; El-Sherbeni and El-Kadi, 2014; Mitra et al, 2011) in addition to P450 2D (Thompson et al, 2000). In contrast, AMMCOD activity, indicative of P450 2D2 activity, was significantly suppressed by OME because the proton pump inhibitor at different concentrations (10 nM-1 µM) did not inhibit formation of the product AHMC when AMMC (substrate) was incubated with liver microsomes from untreated rats in vitro .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although TCDD induces CYP1A1, 1A2, and 1B1 and studies show they can produce 19-HETE, there is no evidence these P450s can produce 20-HETE (Choudhary et al, 2004;El-Sherbeni et al, 2014;Falck et al, 1990;Schwarz et al, 2004). CYP4A12 is the major P450 isoform that generates 20-HETE in male mice (Muller et al, 2007); however, it was not induced by TCDD in either the liver or kidney.…”
Section: Discussionmentioning
confidence: 99%
“…CYP2C11 and CYP2J3 are two main AA epoxygenases in the rat heart (El-Sherbeni et al, 2013). Cardiac CYP1A1, CYP2B1, and CYP2E1 have also been reported to display AA epoxygenase activity (El-Sherbeni and El-Kadi, 2014). CYP1B1 has been found able to metabolize AA into both EETs and 20-HETE simultaneously (Choudhary et al, 2004).…”
Section: Discussionmentioning
confidence: 99%